The influence of extrachromosomal elements in the anthrax “cross-over” strain Bacillus cereus G9241 - Taylor-Joyce, Grace; Manoharan, Shathviga; Brooker, Thomas A.; Hernández-Rodríguez, Carmen Sara; Baillie, Les; Oyston, Petra C. F.; Hapeshi, Alexia; Waterfield, Nicholas R. (Frontiers in Microbiology, 2023)
The Bacillus cereus-Bacillus anthracis 'cross-over' strain Bacillus cereus G9241 carries two virulence plasmids, pBCX01 and pBC210, as well as an extrachromosomal prophage, pBFH1. pBCX01 has 99.6 percent sequence identity to pXO1 carried by B. anthracis and encodes the tripartite anthrax toxin genes and atxA, a mammalian virulence transcriptional regulator. This work looks at how the presence of pBCX01 and temperature may affect the lifestyle of B. cereus G9241 using a transcriptomic analysis and by studying spore formation, an important part of the B. anthracis lifecycle. This work has identified that pBCX01 has a stronger effect on gene transcription at the mammalian infection relevant temperature of 37°C in comparison to 25°C. At 37°C, the presence of pBCX01 appears to have a negative effect on genes involved in cell metabolism, including biosynthesis of amino acids, whilst positively affecting the transcription of many transmembrane proteins. The study of spore formation showed B. cereus G9241 sporulated rapidly in comparison to the B. cereus sensu stricto type strain ATCC 14579, particularly at 37°C. The carriage of pBCX01 did not affect this phenotype suggesting that other genetic elements were driving rapid sporulation. An unexpected finding of this study was that pBFH_1 is highly expressed at 37°C in comparison to 25°C and pBFH1 expression leads to the production of Siphoviridae-like phage particles in the supernatant of BcG9241.